Effects of immuno-related gene polymorphisms on a bispecific antibody targeting colorectal cancer cell. (23rd May 2018) - Zhang, Cong-Min; Yu, Lin-Yu; Lv, Jin-Feng; Gong, Liang; Zhou, Hong-Hao; Chen, Xiao-Ping; Fan, Lan
Background: Colorectal cancer (CRC) represents the third most common type of cancer and the third leading cause of death from cancer around the world. M701 is a CD3/EpCAM bispecific antibody that shows promising cytotoxicity toward CRC cells.Aim: To investigate the influence of immuno-related gene polymorphisms on M701 mediated cytotoxicity to CRC cell HCT116.Method: We analyzed the influence of the effect of M701 on the activation and cytotoxicity of peripheral mononuclear blood cells from 129 healthy volunteers with different genotypes.Result: When incubated with M701, peripheral mononuclear blood cells from CD247 rs2949655 AA homozygotes showed significantly lower cytotoxicity than those from AG/GG heterozygotes.Conclusion: CD247 rs2949655 was significantly associated with the cytotoxicity of M701 to HCT116, which might contribute to personalized medicine of M701.